VACCINATION AGAINST PNEUMOCOCCAL INFECTIONS IN RUSSIAN FEDERATION: SOCIAL AND PHARMACOECONOMIC ASPECTS - A. V. Rudakova; N. I. Briko; Yu. V. Lobzin; L. S. Namazova-Baranova; S. N. Avdeev; G. L. Ignatova; M. P. Kostinov; I. S. Koroleva; R. V. Polibin; I. V. Fomin (Журнал инфектологии, 2018)
Vaccination against pneumococcal infections by 13-valent conjugate vaccine (PCV13) can significantly reduce morbidity and mortality.The study has been aimed to evaluate the social and pharmacoeconomic aspects of PCV13 vaccination of 65-year-old patients with various risks of pneumococcal infection.Material and methods. Markov model with 5 and 15 years time horizon was used for the analysis from the position of the health care system.The analysis was carried out for 65-year-old citizens with low (absence of immunocompromized conditions and chronic diseases), moderate (patients with chronic diseases without immunodeficiency) and high (immunocompromized conditions) risk of pneumococcal infection as well as for the entire population of 65-year-old citizens, regardless of the risk level.In base-case assumption has been made that 1 dose of PCV13 should be administered for the patients from low and moderate risk groups and in the high-risk group 1 dose of PCV13 and in 8 weeks a dose of polysaccharide pneumococcal vaccine (PPV23) should be given.The treatment and physician visit costs have been calculated using CHI rates for St. Petersburg in 2018. Vaccination cost was calculated using the auction price to purchase PCV13 and PPV23 in 2018.Results. Vaccination of 1 cohort of 65-year-old citizens in Russian Federation within 5 years will result in prevention of 2200 deaths, 3900 cases of invasive pneumococcal diseases (IPD) and 48700 cases of community-acquired pneumonia. In 15 years prevention of about 4,3 thousand deaths, 6,6 thousand IPD and 101,1 thousand cases of CAP will be provided.Within 15-year horizon the cost-effectiveness ratio will be RUR 30,3, 82,4 and 410,0 thousand per QALY in high, moderate and low risk groups, respectively. Even if the time horizon is reduced to 5 years the PCV13 vaccination can be considered as an economically high-efficient intervention in moderate and high risk groups (cost-effectiveness ratio - RUR 279,2 and 221,7 thousand / QALY, respectively).In the 15-year-horizon noting the distribution of 65-yearolds by risk levels the cost-effectiveness ratio of PCV13 in population as a whole will be RUR 216,4 thousand / QALY. If moderate and high risk groups only are vaccinated, the average cost-effectiveness ratio will drop to RUR 67,6 thousand /QALY. At universal PCV13 vaccination of 65 years old in 5 year time horizon return of investment to the health care system budget will be 33.2% and at vaccination of persons with moderate and high risk return of investment will be 44.0%. With the assumption of vaccination during the planned physician visit (without additional visit) the return to the budget will be 46.8% and 60.9% for vaccination of all 65-year-olds and patients from the moderate and high risk groups, respectively.Conclusions. Vaccination of the 65-year-old persons against PCV13 pneumococcal infection in Russian Federation can be considered as a highly socially and economically effective intervention resulting in significant reduction of pneumococcal infection incidence and related mortality. The cost-effectiveness of vaccination is increasing along with the level of the risk. PCV13 vaccination of patients with moderate and high risk only provides a significant reduction in the burden for the health care budget in comparison with the vaccination of the entire population of 65-year-olds.